2020
DOI: 10.3390/nu12082334
|View full text |Cite
|
Sign up to set email alerts
|

A High Docosahexaenoic Acid Diet Alters the Lung Inflammatory Response to Acute Dust Exposure

Abstract: Agricultural workers are at risk for the development of acute and chronic lung diseases due to their exposure to organic agricultural dusts. A diet intervention using the omega-3 fatty acid docosahexaenoic acid (DHA) has been shown to be an effective therapeutic approach for alleviating a dust-induced inflammatory response. We thus hypothesized a high-DHA diet would alter the dust-induced inflammatory response through the increased production of specialized pro-resolving mediators (SPMs). Mice were pre-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 66 publications
(94 reference statements)
1
15
0
Order By: Relevance
“…Male 6-8-week-old C57Bl/6 mice were purchased from Jackson Laboratories. After a 1-week acclimation period, mice were placed on a high DHA diet or a control diet lacking DHA, prepared as we have previously described [ 19 , 24 ]. Both the high DHA and standard modified diet were prepared by ENVIGO (Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Male 6-8-week-old C57Bl/6 mice were purchased from Jackson Laboratories. After a 1-week acclimation period, mice were placed on a high DHA diet or a control diet lacking DHA, prepared as we have previously described [ 19 , 24 ]. Both the high DHA and standard modified diet were prepared by ENVIGO (Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Both the high DHA and standard modified diet were prepared by ENVIGO (Madison, WI, USA). Both diets have been utilized in a previous study where we showed the effectiveness of the high DHA diet in altering the lung inflammatory response to a single exposure to HDE [ 24 ]. Briefly, in our study the AIN-93G diet was modified to replace soybean oil with high oleic safflower oil.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of RvD1 in the management of a range of disorders including neurodegenerative diseases ( Krashia et al, 2019 ; Miyazawa et al, 2020 ), fibrotic/electrical remodeling ( Hiram et al, 2020 ), diabetes mellitus and its complications ( Bathina and Das, 2021 ; Bathina et al, 2020 ; Bu et al, 2019 ; Yorek, 2018 ), acute kidney injury ( Luan et al, 2020 ), colitis-associated cancers ( Zhong et al, 2018 ), rheumatoid arthritis ( Özgül Özdemir et al, 2020 ), Sjogren's syndrome ( Yellepeddi et al, 2021 ), ocular allergic responses ( Dartt et al, 2019 ), and polycystic ovary syndrom (PCOS) ( Regidor et al, 2020 ) has shown promising results. In addition, lung diseases that have shown improvement following RvD1 administration include smoking-related asthma and COPD ( Bhat et al, 2020 , 2021 ), acute immune response and fibrotic lesions due to exposure to dust and nanomaterial ( Dominguez et al, 2020 ; Lim et al, 2020 ), lung adenocarcinoma ( Vannitamby et al, 2021 ), and airway inflammation in cystic fibrosis ( Ringholz et al, 2018 ), as well as ARDS. Here, we review the current knowledge on the effectiveness of RvD1 along with its mechanism of action and signaling routes in ALI/ARDS.…”
Section: Introductionmentioning
confidence: 99%